2021
DOI: 10.1021/acschemneuro.0c00728
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioning Induces Neuronal Differentiation of Infrapatellar Fat Pad Stem Cells through Epigenetic Alteration

Abstract: Hypoxia is considered a key factor in cellular differentiation and proliferation, particularly during embryonic development; the process of early neurogenesis also occurs under hypoxic conditions. Apart from these developmental processes, hypoxia preconditioning or mild hypoxic sensitization develops resistance against ischemic stroke in deteriorating tissues. We therefore hypothesized that neurons resulting from hypoxia-regulated neuronal differentiation could be the best choice for treating brain ischemia, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…On the other hand, the overproduction of reactive oxygen species [ 36 , 37 ], and at the next stage, lipid peroxidation [ 38 ], is an integral part of the general “adaptation-stress” syndrome [ 39 ]. In this case, the activation of free radical processes also serves as a nonspecific signal for the mobilization of the body’s defense systems [ 40 , 41 , 42 , 43 ], including the activation of antioxidant defense mechanisms [ 44 ], which is a typical reaction of the biological system to an effect that unbalances it from the state of physiological equilibrium [ 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the overproduction of reactive oxygen species [ 36 , 37 ], and at the next stage, lipid peroxidation [ 38 ], is an integral part of the general “adaptation-stress” syndrome [ 39 ]. In this case, the activation of free radical processes also serves as a nonspecific signal for the mobilization of the body’s defense systems [ 40 , 41 , 42 , 43 ], including the activation of antioxidant defense mechanisms [ 44 ], which is a typical reaction of the biological system to an effect that unbalances it from the state of physiological equilibrium [ 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that preconditioning mesenchymal stem cells with cytokines or speci c conditioned medium can enhance their paracrine functions, including the effects of exosomes on tissue injury and repair (20)(21)(22). In this study, we preconditioned ADSCs for 6 h with IL-1β, one of the vital proin ammatory cytokines induced by LPS, and then collected ADSC-derived extracellular vesicles using a small extracellular vesicles concentration solution kit and supercentrifugation.…”
Section: Isolation and Characterization Of Adsc-derived Sevsmentioning
confidence: 99%
“…Previous studies have shown that preconditioning mesenchymal stem cells with cytokines or specific conditioned medium can enhance their paracrine functions, including the effects of exosomes on tissue injury and repair [20][21][22]. In this study, we preconditioned ADSCs for 6 h with IL-1β, one of the vital proinflammatory cytokines induced by LPS, and then collected ADSC-derived extracellular vesicles using a small extracellular vesicles concentration solution kit and a small extracellular vesicle purification filter.…”
Section: Isolation and Characterization Of Adsc-derived Sevsmentioning
confidence: 99%